DESAIN KURIKULUM PENDIDIKAN AGAMA ISLAM BAGI ANAK DALAM KELUARGA PERSPEKTIF ISLAM - Faizah, Nadjematul (Almarhalah: Jurnal Pendidikan Islam, 2022)
Religious education is education that instills religious values ​​with the teachings of their respective religious beliefs. In the view of Islam, humans are born in a state of carrying nature that needs to be developed. Islam views education in the family as the oldest and most important informal religious education institution. In one part of the Three Education Centers, the role of parents or families in education is very significant among schools and communities. Religious education in the family with an Islamic perspective is education that is applied in the family based on Islamic religious guidance to shape individuals into human beings who believe and fear Allah SWT and have noble character and practice religious values ​​in everyday life. The implementation of religious education for children in the family at an early age has a very large influence, the role carried out in formal educational institutions is not able to take over family institutions in inculcating religious moral values. Therefore, it is very important for parents to understand religious education for their children which is carried out within the family scope.